2003
DOI: 10.1007/bf02967660
|View full text |Cite
|
Sign up to set email alerts
|

A case of diabetic mastopathy with multiple lesions mimicking breast cancer

Abstract: We report a case of diabetic mastopathy with multiple unilateral lesions in an insulin dependent patient. The patient was a 62-year-old woman with two hard tumors in the right breast, who had been treated with insulin for diabetes mellitus. Mammography revealed a highly dense tumor in the right breast, while ultrasonography showed two irregular hypoechoic lesions with marked posterior acoustical shadowing, suggesting scirrhous carcinoma. On magnetic resonance imaging the two lesions had slightly heterogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Diabetic mastopathy is an uncommon tumorlike proliferation of fibrous tissue of the breast, mimicking breast cancer clinically 8,14,15) , and usually occurs in patients with type diabetes mellitus of long duration. Since Soler and Khardori first reported 2 cases of fibrous disease of the breast in association with longstanding type 1 diabetes mellitus in 1984 16) , 168 cases of diabetic mastopathy that occurred in patients with type diabetes mellitus have been reported in 29 papers so far 1-8, 10, 12-31) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetic mastopathy is an uncommon tumorlike proliferation of fibrous tissue of the breast, mimicking breast cancer clinically 8,14,15) , and usually occurs in patients with type diabetes mellitus of long duration. Since Soler and Khardori first reported 2 cases of fibrous disease of the breast in association with longstanding type 1 diabetes mellitus in 1984 16) , 168 cases of diabetic mastopathy that occurred in patients with type diabetes mellitus have been reported in 29 papers so far 1-8, 10, 12-31) .…”
Section: Discussionmentioning
confidence: 99%
“…These appearances are nonspecific and mimic those of scirrhous or invasive lobular carcinoma 19,20,33) . MR imaging findings, although there are only a few reports, vary from no enhancement to slight heterogeneous enhancement of the mass 10,11,13,14) . In our case, MR imaging revealed a blurred contrast enhanced area, which is not typical of malignancy, but malignancy could not be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; DMP is a rare disease in Japanese (9)(10)(11)(12)(13)(14)(15). DMP clinically mimics breast cancer and it is also reported that mastectomy has been performed because it was misinterpreted as breast cancer (7,16 (Fig.…”
Section: Diabetic Mastopathy (Dmp) Is a Benign Fibrous Disease In Brementioning
confidence: 99%
“…1,2 At the time of presentation with breast symptoms, patients often have associated complications of DM such as retinopathy, nephropathy, and neuropathy. 3,4 Histologically, it consists of lymphocytic mastitis and stromal fibrosis. 1,3,4,5 Most published reports on DMP are on premenopausal women with long-standing type 1 DM.…”
Section: Commentsmentioning
confidence: 99%